STATUS AND CAMPAIGN PLAN FOR TOBACCO TAX INITIATIVE. (Tufts Archival Research Center, 2007)
Confidential; Memorandum from A.K. Associates and Paul Kinney to Roger Mozingo and Hurst Marshall reporting on the status and campaign plan for the Tobacco Tax Initiative. Emphasizes importance of defeating a bill to increase the cigarette excise tax despite the lobbying effort of the California Medical Association and other listed organizations.